Pax2 is persistently expressed by GABAergic neurons throughout the adult rat dorsal horn. (18th January 2017) - Larsson, Max
Highlights: Pax2 was expressed in neurons in all laminae of the dorsal horn in the adult rat. GABA immunoreactivity was detected in essentially all Pax2 + neurons. Pax2 immunoreactivity was detected in essentially all GABA + neurons. Pax2 is a robust somatic marker of inhibitory neurons in the adult rat dorsal horn. Persistent Pax2 expression may be required to maintain a GABAergic phenotype. Abstract: The transcription factor Pax2 is required for the differentiation of GABAergic neurons in the mouse dorsal horn. Pax2 continues to be expressed in the adult murine spinal cord and has been used as a presumed marker of GABAergic neurons in the superficial dorsal horn of the adult mouse, although a strict association between adult Pax2 expression and presence of GABA throughout the dorsal horn has not been firmly established. Moreover, whether Pax2 is selectively expressed in GABAergic dorsal horn neurons also in the rat is unknown. Here, immunofluorescent labeling of Pax2 and GABA in the lumbar spinal cord of adult rats was used to investigate this issue. Indeed, essentially all GABA immunoreactive neurons in laminae I–V were immunolabeled for Pax2. Conversely, essentially all Pax2 immunopositive neurons in these laminae exhibited somatic GABA immunolabeling. These results indicate persistent Pax2 expression in GABAergic neurons in the adult rat dorsal horn, supporting the hypothesis that Pax2 may be required for the maintenance of a GABAergic phenotype in mature inhibitory dorsal horn neurons in the rat. Furthermore, Pax2 may be used as a selective and specific general somatic marker of such neurons.